AI-Assisted Citation Training for Undergraduate Students: A Community Engagement Program Using Scite AI and Jenni AI at Universitas Al Irsyad Cilacap - Teguh Iman Santoso (SOCIRCLE : Journal Of Social Community Services, 2026)
Artificial Intelligence has reshaped higher education and academic writing practices, particularly in supporting students’ ability to manage references and citations more efficiently. However, undergraduate students often experience difficulties in identifying scholarly sources, formatting references, integrating citations into academic drafts, and verifying the accuracy of AI-generated citation outputs. This community engagement activity aimed to strengthen students’ academic literacy through an AI-assisted automated citation workshop using Scite AI and Jenni AI. The workshop was conducted online on Saturday, April 25, 2026, through the Faculty of Economics and Business, Universitas Al Irsyad Cilacap, and involved approximately 50 undergraduate students from the Entrepreneurship and Digital Business Program. The activity was implemented through conceptual explanation, live demonstration, hands-on citation practice, manuscript integration simulation, mentoring, and reflective discussion. The results showed that students were able to practice AI-assisted reference searching, generate citations, format reference lists, and integrate citations into short academic writing drafts. The workshop also encouraged students to verify AI-generated outputs, compare citation formats with academic writing standards, and understand the importance of ethical source use. The main outputs of the activity included AI-assisted reference lists, citation-formatted writing drafts, and student reflection on responsible AI use in academic writing. This activity demonstrates that AI-assisted citation training can support students’ scholarly writing skills when combined with practical exercises, output verification, and academic integrity awareness. Follow-up mentoring and integration of AI citation literacy into research writing courses are recommended to sustain students’ citation competence and responsible use of AI tools.